2011
DOI: 10.2320/matertrans.t-m2011807
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Aluminum Coating onto CFRP Substrate by Cold Spray

Abstract: Carbon fiber-reinforced plastic (CFRP) has a great potential application in aircraft fuselage due to its light weight, high specific stiffness and high specific strength. It is crucial to coat the CFRP surface with an electrically conductive material to avoid the damage from lightning strike. Cold spray process has been developed for metallic coating technique. In this study, aluminum coating was fabricated onto the CFRP substrate using interlayer was investigated. It was difficult to fabricate cold-sprayed al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 12 publications
2
47
0
1
Order By: Relevance
“…For this reason, the height of the aluminum coatings is lower than the height of the steel coating. However, it is known from the literature that the particle deformation is a key factor for bonding to occur [33][34][35], meaning that it is very difficult for the upcoming aluminum particles to remove the first layer as it remains firmly anchored to the polymer surface. Hence, the main result obtained is that for CFPP-Al1, the coating deposition seems to be better than the AISI-based coating, and the particles seem to be bonded with the substrate, thus promoting the coating formation and grow-up.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the height of the aluminum coatings is lower than the height of the steel coating. However, it is known from the literature that the particle deformation is a key factor for bonding to occur [33][34][35], meaning that it is very difficult for the upcoming aluminum particles to remove the first layer as it remains firmly anchored to the polymer surface. Hence, the main result obtained is that for CFPP-Al1, the coating deposition seems to be better than the AISI-based coating, and the particles seem to be bonded with the substrate, thus promoting the coating formation and grow-up.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Zhou et al [2] reported difficulties when dealing with cold spray of copper on the same materials. Affi et al [3] reported similar difficulties while spraying on carbon fiber reinforced epoxy.…”
Section: Introductionmentioning
confidence: 89%
“…Metallization of polymers has received increasing attention in a wide range of applications during the past few decades (Ref 1). In the early 1990s, the evolution in microelectronics industry stimulated intensive research on this topic due to the great need for miniaturization and reduction Among these technologies, cold spray has been demonstrated to be a feasible approach to metallize polymers and polymeric composites ( Ref 3,6,7,8,9,10,11,12,13). In particular, cold spray features low processing temperatures, which will minimize the thermal damage to the polymeric substrates compared to other thermal spray technologies.…”
Section: Introductionmentioning
confidence: 99%